Lipopolysaccharide-activated macrophages regulate the osteogenic differentiation of bone marrow mesenchymal stem cells through exosomes - Song,Xiao; Xue,Yiwen; Fan,Siyu; Hao,Jing; Deng,Runzhi (PeerJ, 2022)
Background Periodontal tissue regeneration is the ultimate goal of periodontitis treatment. Exosomes are nanoscale vesicles secreted by cells that participate in and regulate the physiological activities between cells. However, the relationship between inflammatory macrophage-derived exosomes and osteoblast differentiation in periodontitis has not been thoroughly reported. Here, we attempt to explore the role of inflammatory macrophage-derived exosomes in crosstalk with osteoblasts. Methods Porphyromonas gingivalis lipopolysaccharide was used to stimulate macrophages and inflate their inflammatory cellular state. Exosomes were extracted from inflammatory macrophages using supercentrifugation, and their characteristics were detected by transmission electron microscopy, particle size analysis, and Western blotting. Exosome uptake bybone marrow mesenchymal stem cells (BMSCs) was observed by fluorescence microscopy. The effects of exosomes on the BMSC inflammatory response and on osteogenic differentiation were detected by quantitative polymerase chain reaction and Western blot analysis. Alkaline phosphatase activity was tested for verification. Results We successfully extracted and identified inflammatory macrophage-derived exosomes and observed that BMSCs successfully took up exosomes. Inflammatory macrophage-derived exosomes upregulated the expression levels of the inflammatory factors interleukin-6 and tumour necrosis factor-alpha in BMSCs and mediated inflammatory stimulation. Additionally, they inhibited the transcription levels of the osteogenic genes alkaline phosphatase, type I collagen, and Runt-related transcription factor 2 as well as the alkaline phosphatase activity, while the use of the exosome inhibitor GW4869 attenuated this effect. Conclusion Our study shows that macrophages in periodontitis can mediate inflammatory stimulation and inhibit the osteogenic differentiation of bone marrow mesenchymal stem cells through the exosome pathway. Interference with exosome secretion is likely to be a promising method for bone tissue regeneration in inflammatory states.
Keywords: Exosome; Periodontitis; Macrophage; Stem cell; Osteogenesis differentiation